Effects of source and level of dietary lysine on growth performance of pigs from 24 to 48 lb - Hansen, E.L.; Woodworth, J.C.; O'Quinn, P.R.; De La Llata, M.; Steidinger, M.U.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred twenty, 24 lb nursery pigs were fed for 19 days to compare the effects of increasing dietary lysine from L-Iysine HCl (L-Lys) or Peptide Plus™ (PP) on growth performance. Three dietary treatments (1.025, 1.15, and 1.275% lysine) were each formulated with L-Lys and PP. Negative and positive control corn-soybean meal-based diets were formulated to .90 and 1.275% lysine, respectively. Increasing dietary lysine to 1.275% from L-Lys or PP resulted in increased performance; however, pigs fed the positive control diet had the best overall performance.
Keywords: Swine; Lysine; L-lysine HCl; Peptide plus; Pigs